Perspektif kompetensi antarabudaya: satu kajian fenomenologi - Dalib, Syarizan (2016)
Studies in intercultural competence are quite numerous but they were mainly derived from Western experiences.Since Western scholars may become oblivious to certain elements or issues of intercultural communication that are pertinent to Asian people, the Western conception of intercultural competence have been argued for its relevance in the Asian world.This paper aims to revisit the current (Western) perspective of intercultural competence by considering intercultural experiences that are situated within a Malaysian setting.This paper specifically probes the conception of intercultural competence that is draw from a series of reflection on lived intercultural experiences of fifteen culturally diverse students in a Malaysian campus through phenomenological method.The findings suggest that intercultural competence constitutes three core themes: mutual understanding, mutual respect, and language ability.This study brings forth an alternative outlook that contributes into a re-conceptualization of intercultural competence from the Malaysian context.